The Starry Heavens Above Me and the Starmaking Power Within Me - (:unkn) unknown (My University, 2013)
The worldmaking thesis stands as a contentious view of reality. Its primary tenet, that we play a role in cognitively making objects, properties, facts, and thereby the world, is dismissed by many philosophers as an incoherent and misguided position. In this paper I critically discuss the thesis and defend it against several criticisms: that (1) it is cosmologically incoherent, (2) raises a problem of causation, (3) implies subjectivism, (4) commits a use-mention fallacy, and (5) it commits the problem of disagreement. I show that these criticisms are not ultimately deleterious to the thesis. Furthermore, I explore ways in which worldmaking constitutes a more satisfactory account of objects, properties, and facts over and against competing views, viz., metaphysical realism.